Pembaruan Maslaḥah dalam Maqāṣid Al- Sharī‘ah: Telaah Humanistis tentang Al-Kulliyyāt Al-Khamsah - Zaenuddin Mansyur (Ulumuna, 2012)
In order to answer a variety of issues faced by human being in the current era, such as human rights abuses, social disintegration, and terrorism, the renewal of Islamic law in the level of theoretical and practical aspects is very urgent. This paper aims to examine one of the Islamic legal reform efforts, namely to build a more technical understanding of the concept of maṣlaḥah contained in the maqāṣīd sharī‘ah, called the al-kulliyat al-khamsah. Therefore, the concept of maṣlaḥah in ḥifẓ al-dīn is technically defined as al-ḥurriyah al-i‘tiqād (freedom of religion and schools); in ḥifẓ al-nafs as al-karamat al-insān (human being breeding); in ḥifẓ al-nasl as ḥifẓ al-usrah (wholeness and harmony of the family); in ḥifẓ al-māl as al-taḍammun al-insān (social solidarity ), and in ḥifẓ al-‘aql as al-ḥuqūq as al-tarbiyāt (increasing human resources quality).